Post-Translational Modifications Modulate Proteinopathies of TDP-43, FUS and hnRNP-A/B in Amyotrophic Lateral Sclerosis - Farina, Stefania; Esposito, Francesca; Battistoni, Martina; Biamonti, Giuseppe; Francia, Sofia (Frontiers in Molecular Biosciences, 2021)
It has been shown that protein low-sequence complexity domains (LCDs) induce liquid-liquid phase separation (LLPS), which is responsible for the formation of membrane-less organelles including P-granules, stress granules and Cajal bodies. Proteins holding LCD are widely represented among RNA binding proteins often mutated in ALS. Indeed, LCD predispose proteins to a prion-like behaviour due to its tendency to form amyloid-like structures typical of proteinopathies. Protein post-translational modifications (PTMs) can alter phase transition through two main events: i) destabilizing or augmenting multivalent interaction between phase-separating macromolecules; ii) recruiting or excluding other proteins and/or nucleic acid into/from the condensate. In this manuscript we summarize the existing evidence describing how PTM can modulate LLPS thus favouring or counteracting proteinopathies at the base of neurodegenerations in ALS.